Environment×Combining Ability Interaction for Quality Traits in Tomato (Solanum lycopersicum L.) - Bhandari, H. R.; Srivastava, K.; Tripathi, M. K.; Chaudhary, B.; Biswas, S.; Shreya (International Journal of Bio-resource and Stress Management, 2021)
The multilocational studies were conducted to evaluate 21 hybrids of tomato in Pratapgarh(Uttar Pradesh), Varanasi (Uttar Pradesh) and Burdwan (West Bengal), India during August–February of 2015–16 and 2016–17. Data on four quality traits viz., total soluble solids, titrable acidity, carotene content and lycopene content were estimated. Combined analysis of variance (ANOVA) revealed significant effects of locations, genotypes, genotype-location interaction and parents vs hybrids-location interaction for all the traits. The significance of combining ability effects (general combining ability and specific combining ability) and their interaction with location revealed environmental influences on combining ability effects for all the traits. The Present study indicated higher estimates of to , lower estimates of heritability and GCA/SCA ratio for quality traitsandthereby implied preponderance of non-additive gene action in determination of quality traits studied. Desirable parental lines were identified for different traits like EC 620438 and BS 24-2 for TSS, BS 24-2 and Superbug for titrable acidity, Columbia, EC 620438 and Superbug for carotene content, and H 86 and EC 620541 for lycopene content. Similarly, desirable specific combiners for different traits were identified. The hybrid combination EC 620438×BS 24-2 appeared good specific combiner for TSS, carotene and lycopene content. The parental lines/hybrids identified in present study will be useful in identifying hybrids adapted to a range of environments.